Real-time mass flow rate measurement for bulk solid flow using electrodynamic tomography system - Yaw, Wee Lee (2007)
In order to increase the efficiency of energy and raw materials usage and to improve product quality and process efficiency, the demand of continuous monitoring of the flow rate of solids in pneumatic pipelines is rising in many industrial areas. This requirement can only be achieved by installing a proper realtime measurement system. Electrodynamic sensor offers the most inexpensive and simplest means of measuring solids flows in pipes. As electrostatic sensors respond only to moving solids in the pipe, the measured data enjoy a large degree of immunity from the effects of solids accretion which adversely affect other technologies. For the developed measurement system, sixty-four channels of KPCI- 1802HC are used to capture the output voltages of thirty-two sensors. The sampling frequency is 1 kHz for each channel. Data per frame was collected over 156 ms. The distance between upstream and downstream sensors is 5 cm. The falling distance of material is set to 1.4 m. Linear back projection algorithm (LBP) and filtered back projection algorithm (FBP) are implemented for image reconstruction. The tomographic technique will generate the real-time concentration profile of the sensing volume. Subsequently, real-time pixel-to-pixel velocity profile can be calculated from cross-correlation of two set of time series that obtained from a number of upstream and downstream concentration profiles. By combining the concentration profile with corresponding velocity profile, mass flow rate profile can be generated. The summation of all pixels value in the mass flow rate profile is carried out to obtain a total value of pixels. The mass flow rate of the solids flow can be calculated by substituting the total value into mass flow rate equation. The dedicated software for the electrodynamic tomography system is developed using Microsoft Visual C++ 6.0. The developed software supports real-time mode and offline mode of the system. The results obtained from the experiments are presented and compared with the calculation of MATLAB. To conclude, a real-time mass flow rate measurement system using elctrodynamic tomography is developed successfully.